Teaching an old dog new tricks: The case of Fenbendazole. (2022) - Vlachou, Ioanna; Parsonidis, Panagiotis; Mamagkaki, Alexandra; Bouris, Ioannis; Papasotiriou, Ioannis
Highlights: Fenbendazole has similar mechanism of action to some anticancer drugs. Qualitative and quantitative analysis of formulated fenbendazole indicates some formulation issues that hinder distribution. Fenbendazole exhibits cytotoxic effect against human cancer cell lines. Abstract: The objective of this study is the assessment of the cytotoxic effect of fenbendazole and its commercially available formulation, which is used for its antihelmintic properties. The formulation was tested for its efficacy as well as the determination of the ingredients with proliferation assays and analytical techniques. HPLC, LC-MS and NMR confirmed the stated amount of active ingredient on the label. Dissolution studies were performed to simulate the ability of fenbendazole to dissolve adequately in the fluids of the Gastrointestinal tract, be absorbed in the circulation and reach certain areas of the human body. However, dissolution studies showed that both brands possess issues in their distribution. The in vitro drug screening exhibited potential cytotoxic effect in different types of human cancer cell lines and MDA-MB-231 human breast adenocarcinoma cells appeared to be the most sensitive with IC50 value lower than 10 μM.